Liikuntateknologiat jääkiekon kenttäpelaajien mittaamiseen ja seurantaan jääharjoitteluiden sekä otteluiden aikana - Laukkanen, Jesse (2024)
Over the years, ice hockey players have been tested in many different ways, both on and off the ice. The aim of this testing has been to understand the versatile characteristics of ice hockey players using a variety of sports technology methods. This thesis aimed to find out how to measure and monitor ice hockey players using sports technology during on-ice practices and matches. In addition, the study aimed to find out what information these sports technology methods provide in concrete terms to ice hockey players and how this information can be used in practice. Based on the study, the sports technologies used during on-ice practices can be divided into timing technologies, motion imaging technologies, wearable technologies, and other technologies. Fewer sports technologies were used during ice hockey matches than during on-ice practices. The sports technologies used during ice hockey matches were local positioning systems, wearable technologies, internal load monitoring technologies, and analysis software. The use of sports technologies appears to offer the user additional information on features when used with experts. This addition-al information can be used, for example in collaboration with the coach, to develop the features of the ice hockey player, which could potentially improve the player's performance during matches, and possibly also the whole team’s performance. The thesis was conducted as a systematic literature review.